Cerebrospinal Fluid Proteomics in Friedreich Ataxia Reveals Markers of Neurodegeneration and Neuroinflammation - Imbault, Virginie; Dionisi, Chiara; Naeije, Gilles; Communi, David; Pandolfo, Massimo (Frontiers in Neuroscience, 2022)
Clinical trials in rare diseases as Friedreich ataxia (FRDA) offer special challenges, particularly when multiple treatments become ready for clinical testing. Regulatory health authorities have developed specific pathways for “orphan” drugs allowing the use of a validated biomarker for initial approval. This study aimed to identify changes in cerebrospinal fluid (CSF) proteins occurring in FRDA patients that may be potential biomarkers in therapeutic trials. CSF was obtained from 5 FRDA patients (4 females, 1 male) from the Brussels site of the European Friedreich Ataxia Consortium for Translational Studies (EFACTS). Two patients were ambulatory, three used a wheelchair. Residual CSF samples from 19 patients who had had a lumbar puncture as part of a diagnostic workup were used as controls. All CSF samples had normal cells, protein and glucose values. Proteins were identified by label-free data-dependent acquisition mass spectrometry (MS) coupled to micro-high performance liquid chromatography. We found 172 DEPs (92 up, 80 down) between FRDA patients and controls at P<0.05, 34 DEPs (28 up, 6 down) at P<0.0001. Remarkably, there was no overlap between FRDA patients and controls for seven upregulated and six downregulated DEPs. Represented pathways included extracellular matrix organization, signaling, the complement cascade, adhesion molecules, synaptic proteins, neurexins and neuroligins. This study supports the hypothesis that the quantitative analysis CSF proteins may provide robust biomarkers for clinical trials as well as shed light on pathogenic mechanisms. Interestingly, DEPs in FA patients CSF point to neurodegeneration and neuroinflammation processes that may respond to treatment.